Graphene field-effect transistor based high sensitive sensor - Zhao, Haoyu (Nanyang Technological University, 2022)
Sensor is a detection device that can feel the measured signal and convert it into measurable signal output. As an extension of human sense, sensors can help human beings obtain all kinds of information in the universe, become the front end of modern information processing, and are the basis for realizing the era of interconnection, sensibility, measurability, controllability and intelligence. Especially with the proposal and rapid development of new concepts and applications such as Internet of things, smart city and smart car, sensor technology has become particularly important. The discovery of graphene in 2004 has aroused the keen attention of scientific and industrial circles. The research based on the new two-dimensional material graphene is also considered to be a new generation of revolutionary wave that can sweep the electronics industry. Graphene has great research potential and application prospects in the field of optoelectronic devices, especially photovoltaic devices, due to its ultra-high electron mobility, high transmittance and ultra wideband light absorption.